The Influence of School-Based Management and Leadership on Student Academic Achievement: The Mediating Role of Teacher Performance - Nayya Uswa Qonita Rahman; Lukman Hakim (Mozaic : Islam Nusantara, 2025)
This study aims to analyse the effect of School-Based Management (SBM) and the leadership style of school principals on teacher performance and its implications for student academic achievement at SMK Tarbiyatunnasyiin Jombang. The research uses a correlational quantitative approach with a field research design, where data is collected through questionnaires, observations, and literature studies. The analysis is carried out using a statistical model to determine the direct and indirect relationships between variables. The results show that School-Based Management (SBM) plays an important role in improving academic achievement by strengthening teacher performance. In addition, the principal’s leadership style has an influence on improving teacher performance, although it does not directly have a significant effect on student academic achievement. Thus, the combination of effective SBM implementation and participatory leadership by the principal is a key factor in creating optimal teacher performance and improving the quality of education in schools. Theoretically, this research enriches the study of adaptive, collaborative, and quality-oriented Islamic education management. Practically, the results of this study can be used as a reference for school principals and education policymakers in developing leadership strategies and school management that focus on empowering teachers and improving student learning outcomes.